Pengembangan Perangkat Pembelajaran Biologi Berorientasi Konstruktivisme Bernuansa Karakter Pada Materi Sistem Sirkulasi - Rescha Rescha (Symbiotic: Journal of Biological Education and Science, 2024)
Successfull learning can be achieved by learning equipment that involve students actively construct knowledge through meaningful experiences, social interaction, and the real fact. One of the learning equipments to help students build a relationship between the knowledge and its application in real life is learning equipment by constructivist oriented and integrated by nation’s cultural character values. But in reality, in SMAN 1 Sawahlunto, SMAN 8 Padang, and SMA dr. M. Natsir in Solok Regency, learning equipment do not encourage independence in structured thinking and do not integrate character values. The aim of this study was to develop Biology learning equipment by constructivist oriented and character nuanced, consist of the syllabus, lesson plans, handouts, students’ worksheets, and classroom-based assessment on blood circulation system materials for high school grade XI that were valid, practical, and effective. This research using 3-D models. The data collected through validating by five experts and two practitioners then it was tried out in eleventh grade of natural science at SMAN 1 Sawahlunto. The result research results, it was known that Biology learning equipment by constructivist oriented and character nuanced on blood circulation system material for senior high schools grade XI was categorized valid, practical, and effective.